The legend - Grant, Donna (Grant, Donna. Sons of Texas., 2017)
"Callie Reed doesn't need a man to protect her. An expert sharpshooter and renegade hacker, this Texas-born spitfire's got the skills and the courage to stand up to any danger--no matter how deadly. But when she becomes the target of a shadowy organization known as the Saints, Callie is forced to team up with the one man she can't outshoot: the gorgeous and infuriating Lone Star legend named Wyatt Loughman"--Amazon.com.